The Boundedness for a Class of Rough Fractional Integral Operators on Variable Exponent Lebesgue Spaces (Analysis in Theory and Applications, 2012)
In this paper, we will discuss the behavior of a class of rough fractional integral operators on variable exponent Lebesgue spaces, and establish their boundedness from $L^{p_1(·)}(R^n)$ to $L^{p_2(·)}(R^n)$.
Keywords: fractional integral; rough kernel; variable exponent Lebesgue space.